OPTIMALISASI DOKTER KECIL SEBAGAI PEER EDUCATOR TENTANG MANAJEMEN KEBERSIHAN MENSTRUASI (MKM) - Aisyaroh, Noveri; Sutrisminah, Emi (Jurnal LENTERA, 2025)
Menstruation is a sign that adolescent girls are entering puberty, which indicates that reproductive abilities have begun. During menstruation it is important to maintain cleanliness to avoid reproductive health problems, low knowledge can be detrimental to adolescent girls because the practice of MHM becomes incorrect. The purpose of this activity is to increase the knowledge of elementary school students about MHM through small doctors so that they can perform MHM properly during menstruation. Methods: the activity was in the form of health education on small doctors for a total of 25 elementary school students in Semarang City with one group pre and post test design, then Wilcoxon Test analysis was carried out with p <0.05. results: The mean post test knowledge (0.92 ± 0.277) was higher than the mean pre test knowledge (0.40 ± 0.500). The results of the Wilcoxon Test analysis obtained a value of p<0.05 (p=0.002), meaning that there was a significant difference between the mean pre-test and post-test. The importance of knowledge about MHM for little doctors as a provision in providing education to their peers correctly and confidently.